Venerable Ānanda and His Insight Meditation (Vipassanā) - Vimala, Venerable; Techapalokul, Soontaraporn (The Journal of International Buddhist Studies College, 2019)
There were eighty great disciples of the Buddha. Among them who were conferred one or two titles (etadagga), Venerable Ānanda was uniquely conferred totally fi ve titles. Also, among those who were attendants to the Buddha, he was an excellent attendant to the Buddha due to his past wishes. This present paper aims to study the practice that underlines insight meditation of Venerable Ānanda in the Tipiṭak and explore his meditative method which he attained sotapattiphala till arahatphala. The fi nding shows that he served his life for the Buddhist religion throughout his whole life. He led in reciting Suttanta Piṭaka at the First Buddhist Council. Through meditation, he could escape from the circle of birth and help people with insight meditation and answer their questions and doubts on meditation. Venerable Ānanda has been a remarkable monk until now. His role was still crucial for lasting the teachings of the Buddha (sāssana).